Psychological features of patients with chronic non-infectious hepatological pathology - Skurat Катерина (Psychosomatic Medicine and General Practice, 2019)
Introduction. The prevalence of chronic liver disease (CLD) is over 30 million people worldwide, and it is growing rapidly due to the steady increase in the incidence of obesity-related liver disease. CLD can have a variety of etiologies. Chronic liver disease increases the socio-economic burden on patients, their families and the health care system. CLD is associated with significant health care costs, loss of work productivity and/or disability, and significantly affects patients’ quality of life. In recent years, the mental health of patients, including those with CLD, has been actively studied since its impairment leads to a decrease in quality of life, which is associated with deteriorating treatment outcomes, reduced compliance toward treatment and increased mortality. Aim. Determining the current state of analysis of the psychological characteristics of patients with chronic liver disease, systematization of the data and comparison of information presented in the Ukrainian and foreign scientific literature on this issue in recent years. Methods and materials. A qualitative and quantitative content analysis of scientific Ukrainian and English literature published for the period from 2014 to 2019 was conducted, which sets out different views on the psychological characteristics of patients with chronic non-infectious liver pathology. The search was performed using the PubMed database. To analyze the views of world researchers on the psychological characteristics of patients with chronic non-communicable liver disease, it was decided to include only review articles, concept analyzes, meta-analyses and systematic reviews published in English, presented in the scientific literature. Conclusion. This review summarizes information about the psychological characteristics of patients with chronic non-communicable liver disease. Based on the above, we can conclude that this group of patients is characterized by low mood, chronic fatigue, low level of social adaptation, increased anxiety and reduced efficiency. Studies by different scientists from different countries agree that patients with chronic liver disease are characterized by the above symptoms. However, no exact explanation has yet been found as to what exactly caused this. Some emphasize psychoneurophysiology and associate these symptoms with chronic inflammation, which is seen as the liver damage progresses. Other researchers have suggested that this is due to the quality of life of these patients and the burden of the disease.